2018
DOI: 10.7717/peerj.5359
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk derived skimmed milk powder and whey protein concentrate modulatesCitrobacter rodentiumshedding in the mouse intestinal tract

Abstract: Skimmed milk powder (SMP) and whey protein concentrate (WPC) were manufactured from fresh milk collected from cows producing high or low Immunoglobulin (Ig) A levels in their milk. In addition commercial products were purchased for use as diluent or control treatments. A murine enteric disease model (Citrobacter rodentium) was used to assess whether delivery of selected bioactive molecules (IgA, IgG, Lactoferrin (Lf)) or formulation delivery matrix (SMP, WPC) affected faecal shedding of bacteria in C. rodentiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Generally, there are four types of bovine caseins and classified as αs1-casein, αs2-casein, β-casein and κ-caseins [2] . Among these four types of caseins, α-caseins (including αs1-casein and αs2-casein) are the most abundant form of casein in bovine milk [1] . Importantly, α-caseins have been reported to be involved in a variety of physical or pathological conditions, with αs1-and αs2subtypes playing redundant but usually distinct roles [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there are four types of bovine caseins and classified as αs1-casein, αs2-casein, β-casein and κ-caseins [2] . Among these four types of caseins, α-caseins (including αs1-casein and αs2-casein) are the most abundant form of casein in bovine milk [1] . Importantly, α-caseins have been reported to be involved in a variety of physical or pathological conditions, with αs1-and αs2subtypes playing redundant but usually distinct roles [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Casein expression level is an important index when evaluating the lactation function of the mammary gland. While mAbs against β-casein [10] and κ-casein [11] have been developed, no studies have reported the successful development of mAbs against αs1-casein, the major part (38%) of total caseins in milk [12] . In addition, considering that αs1-casein is the most important protein causing milk allergy [13] , mAbs with high specificity to goat αs1-casein are therefore of critical importance for people to avoid milk allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Several forms of pharmaceutical preparations were prepared and used for research, and many pharmaceuticals were manufactured BC. These formulations are: powder in capsule (bovine immunoglobulin concentrate) 52 ; oral bovine colostrum tablet [53] ; sublingual colostrinin tablet 54 intravaginal gel containing purified (dialyzed lyophilized) bovine colostrum (ZP-025) 55 ; spray-dried BC 56 ; and liposomal bovine colostrum. 36…”
Section: Nutriceutical Formulations Are Availablementioning
confidence: 99%